How well do revegetation plantings capture genetic diversity?. (16th October 2019) - Jordan, Rebecca; Breed, Martin F.; Prober, Suzanne M.; Miller, Adam D.; Hoffmann, Ary A.
Abstract : Revegetation plantings are a key management tool for ecological restoration. Revegetation success is usually measured using ecological traits, however, genetic diversity should also be considered as it can influence fitness, adaptive capacity and long-term viability of revegetation plantings and ecosystem functioning. Here we review the global literature comparing genetic diversity in revegetation plantings to natural stands. Findings from 48 studies suggest variable genetic outcomes of revegetation, with 46% demonstrating higher genetic diversity in revegetation than natural stands and 52% demonstrating lower diversity. Levels of genetic diversity were most strongly associated with the number of source sites used—where information was available, 69% of studies showing higher genetic diversity in revegetation reported using multiple provenances, compared with only 33% for those with lower diversity. However, with a few exceptions, it was unclear whether differences in genetic diversity between revegetation and natural stands were statistically significant. This reflected insufficient reporting of statistical error and metadata within the published studies, which limited conclusions about factors contributing to patterns. Nonetheless, our findings indicate that mixed seed sourcing can contribute to higher genetic diversity in revegetation. Finally, we emphasize the type of metadata needed to determine factors influencing genetic diversity in revegetation and inform restoration efforts.